2017
DOI: 10.1111/rego.12153
|View full text |Cite
|
Sign up to set email alerts
|

Passing the buck? Analyzing the delegation of discretion after transposition of European Union law

Abstract: This article seeks to map and explain the extent to which national legislators constrain discretion contained in European Union directives during transposition. To this end, we use standard hypotheses from the domestic delegation literature regarding the necessity of policy conflict and transaction costs. Our empirical approach is based on a focused comparison of the transposition of several provisions of the Asylum Reception Conditions Directive in France, Germany, and the Netherlands. In order to capture con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…For the purpose of this study, the policy field of migration is selected, in which national principals typically aim to stay in control of EU law interpretation. Although Dörrenbächer and Mastenbroek (in press) have shown that national transposition actors also sometimes delegate EU discretion down to practical implementers, they highlight that transposition actors typically do so to maintain administrative and legal structures. In the field of migration, discretion is typically not delegated to explicitly encourage frontline implementers to circumvent national instructions or to leave interpretations to the frontline.…”
Section: Theory Section: An Organisational Perspective On Frontline Umentioning
confidence: 99%
“…For the purpose of this study, the policy field of migration is selected, in which national principals typically aim to stay in control of EU law interpretation. Although Dörrenbächer and Mastenbroek (in press) have shown that national transposition actors also sometimes delegate EU discretion down to practical implementers, they highlight that transposition actors typically do so to maintain administrative and legal structures. In the field of migration, discretion is typically not delegated to explicitly encourage frontline implementers to circumvent national instructions or to leave interpretations to the frontline.…”
Section: Theory Section: An Organisational Perspective On Frontline Umentioning
confidence: 99%
“…It is evident that public actors cannot master the challenges associated with youth unemployment by themselves, and they have therefore designed arrangements in which private actors provide support. We could also observe this trend in other areas of state action, such as migration (see Dörrenbächer and Mastenbroek, 2019). Our study has shown that both a hierarchical structure of national political economy and prior expenditure in ALMPs affect the extent to which private actors are included in the implementation of the Youth Guarantee.…”
Section: Discussionmentioning
confidence: 52%
“…As a result, the extent to which the frontline bureaucracy relies on EU law varies and produces different administrative decisions. EU law delegates discretion to practical implementers, 'who thus become, in essence, EU lawmakers' (Dörrenbächer & Mastenbroek, 2017). Implementers are creative and flexible when using legal tools, which leads to variation in implementation practices.…”
Section: Street-level Implementation and Judicial Impactmentioning
confidence: 99%